The Similarities and Nuances of Explicit Design Characteristics of Well-Received Online Instructional Animation - Lucas, Terry; Ruslan, Abdul Rahim (SAGE Publications Ltd, 2017)
Online learning is becoming more prevalent throughout the years and there are various methods available to learn via the internet, one of which is by watching educational videos from online streaming sites such as YouTube. With the increasing availability of instructional animations on the internet, it can be beneficial to know how well-received instructional animations are designed. Hence, this explorative article focuses on a hybrid of directed and interpretive content analysis study of explicit design characteristics and visual representations of these animations. Animation samples for the study were selected from established educational animation content creators on YouTube using several criteria. Aspects such as design characteristics and visual representations were analysed and discussed in relation to the Cognitive Theory of Multimedia Learning principles and a characterization system of expository animation. Based on this approach, common characteristics and unique approaches to creating well-received instructional animations for online viewing are found. Thus, by being able to identify and being aware of these salient design characteristics (i.e. visual representations, sound and visual cues), educators and animation designers can incorporate them in their own instructional animations.